2020
DOI: 10.5191/jiaee.2020.273116
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Agricultural Communication Interventions on Improving Agricultural Productivity in Malawi

Abstract: Agricultural communication (AGCOM) has been known to aid in disseminating research-based agricultural information among Malawian farmers. In 1958 the Malawi Government, via the Ministry of Agriculture, established the Agricultural Communications Branch (ACB) in an attempt to increase access to and adoption of scientifically-proven technologies among farmers. Moreover, in 2000 the Malawi Government started implementing an agricultural extension policy that promoted pluralistic demand-driven extension, which led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Extension services provided by the government through sectors such as agriculture, forestry, fisheries, disaster risk reduction, and overall environmental management practices play an important role in providing public information on development projects and policies to improve rural livelihood. Pluralism in extension service provision has enabled other players, NGOs, to expand their work in rural development (Masangano and Mthinda 2012;Masambuka-Kanchewa et al 2020). Malawi's informal rural communication structures are mostly interpersonal and heavily influenced by traditional communication techniques, social ties, and social networks.…”
Section: Rural Communication Landscape In Malawimentioning
confidence: 99%
“…Extension services provided by the government through sectors such as agriculture, forestry, fisheries, disaster risk reduction, and overall environmental management practices play an important role in providing public information on development projects and policies to improve rural livelihood. Pluralism in extension service provision has enabled other players, NGOs, to expand their work in rural development (Masangano and Mthinda 2012;Masambuka-Kanchewa et al 2020). Malawi's informal rural communication structures are mostly interpersonal and heavily influenced by traditional communication techniques, social ties, and social networks.…”
Section: Rural Communication Landscape In Malawimentioning
confidence: 99%
“…Compatibility of an innovation to the existing social norms, beliefs, previously introduced ideas and past experiences is one of the most important characteristics that can slow or improve adoption of an innovation (Rogers, 2010). Diffusion of innovations theory is often used to understand how new agricultural ideas, perceived as only originating from scientists, diffuse into society; therefore, an emphasis has been placed on the diffusion of scientific innovations by various governments and decision makers as they strive to create policy (Briggs and Moyo, 2012;Masambuka-Kanchewa et al, 2020;Rogers, 2010). However, such an approach ignores the importance of disseminating IK which is locally produced and available among members of the community.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Despite political reforms designed to improve direct access to information, agricultural extension agents, and associated advisory service providers, largely focus on the adoption of new, scientifically proven technologies with extension agents often perceived by farmers as improved technology promoters rather than as educators (Benson and Jafry, 2013;Masangano et al, 2017;Ragasa and Chiyu, 2017). The technology promotion approach has reinforced the perceptions that farmers are solely recipients of agricultural advice and not information generators or conduits (Masambuka-Kanchewa et al, 2020). Therefore, not much is known regarding the role of traditional or indigenous knowledge (IK) in promoting sustainable agricultural development in the SSA region, as well as how it is informed by the policy.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have found a positive relationship between the use of ICT-based agricultural extension tools and increased productivity (Gebru et al, 2019;Masambuka-Kanchewa et al, 2020). Evidence from studies done in Malawi and elsewhere shows that there are many factors that affect the adoption of ICTs among farmers.…”
Section: Factors Affecting Adoption Of Ict Among Farmersmentioning
confidence: 99%